Education-based interventions for anxiety during the treatment and management of chronic disease: a systematic review protocol. Issue 11 (3rd November 2020) - Koeppen, Jordeah; Sinclair, Peter M.
ABSTRACT: Objective: The objective of this systematic review is to evaluate the effectiveness of education-based interventions to decrease patient anxiety during the treatment and management of a chronic disease. Introduction: Anxiety is a major contributor to poor patient outcomes in self-managed chronic disease. Health care manage anxiety prior or during education can adversely affect patient outcomes. By identifying interventions that effectively decrease anxiety, clinicians may be able to consider and implement strategies as standard practice within the education-based programs. Inclusion criteria: The proposed systematic review will consider studies reporting the effectiveness of any intervention aimed at decreasing participant anxiety prior to a medical procedure or prior to undertaking an education-based program to address a technical aspect of self-management in a health care setting. It will consider studies whose participants are 18 years and older and who are diagnosed with a chronic disease. Methods: The systematic review aims to find published and unpublished studies in English from 1972 onward. Databases to be searched included MEDLINE, CINAHL, Embase, ERIC, Mosby's index, Cochrane Library, and Scopus. Studies will be reviewed and data extracted by two independent reviewers. The data will include details about the interventions, populations, study methods, and outcomes of significance to the review objectives. Where possible, data will be pooled in a statistical meta-analysis. Systematic review registration number: PROSPERO CRD42019142260